Transformasi Perencanaan Pembelajaran Guru melalui Pelatihan Perangkat Mengajar dan Asesmen Autentik Berbasis Pembelajaran Mendalam: Pengabdian - Nurfaisal; Herlinawati; Junaidi; Muliardi; Firdaus; Ardiyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to transform teachers’ instructional planning through training on lesson plan development and authentic assessment grounded in deep learning pedagogy. The program was conducted at SMA Negeri 3 Tambusai Utara, Rokan Hulu Regency, on 19–20 November 2025 and involved 33 teachers from grades X–XII. A collaborative training and mentoring approach was employed, including brainstorming sessions, lectures, group discussions, and hands-on practice in developing instructional plans and performance-based assessment rubrics. Data were collected through observations of the training process, document analysis of the lesson plans and assessment rubrics produced by participants, and activity documentation. The results indicate a shift in teachers’ perspectives from an administrative to a pedagogical orientation in instructional planning. Teachers demonstrated improved ability to design more contextual, coherent, and competency-oriented lesson plans, as well as to integrate authentic assessment and formative feedback into instructional design. The training also contributed to enhanced assessment literacy and strengthened teachers’ roles as learning designers within deep learning–oriented instruction.